1998
DOI: 10.2134/agronj1998.00021962009000040013x
|View full text |Cite
|
Sign up to set email alerts
|

Rotation and Fertilization Effects on Corn and Soybean Yields and Soybean Cyst Nematode Populations in a No‐Tillage System

Abstract: Rotations have long been used to improve crop yields. No‐tillage production acreage is increasing, and production information on rotation effects on yields and soybean cyst nematode populations is needed for this system. Field experiments were initiated in 1985 and continued through 1992 to evaluate P‐K fertilization effects on yield of a corn‐soybean [Zea mays L.‐Glycine max (L.) Merr.] rotation and on populations of soybean cyst nematode (Heterodera glycines Ichinohe) (SCN). The research was conducted on a L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 10 publications
1
27
0
Order By: Relevance
“…Rotating crops may alter the environment in which weeds are adapted, thereby reducing weed populations (Higgs et al, 1990). Several studies have shown reductions in soybean cyst nematode (Heterodera glycines) populations when soybean is rotated with a non-host crop such as corn (Howard et al, 1998;Chen et al, 2001). Specifically, Sclerotinia stem rot in soybean is reduced when cropping rotations are implemented (Kurle et al, 2001).…”
Section: Impact Of Crop Rotations and Soil Amendments On Long-term Nomentioning
confidence: 99%
“…Rotating crops may alter the environment in which weeds are adapted, thereby reducing weed populations (Higgs et al, 1990). Several studies have shown reductions in soybean cyst nematode (Heterodera glycines) populations when soybean is rotated with a non-host crop such as corn (Howard et al, 1998;Chen et al, 2001). Specifically, Sclerotinia stem rot in soybean is reduced when cropping rotations are implemented (Kurle et al, 2001).…”
Section: Impact Of Crop Rotations and Soil Amendments On Long-term Nomentioning
confidence: 99%
“…Management practices, including tillage, fertilizer input, and plant rotation, have been reported to have signifi cant eff ects on agricultural systems, including weed community (Swanton et al, 2006), soil structure (Grandy et al, 2006b;Wright and Hons, 2004), soil fertility (Kelley and Sweeney, 1998), crop yield, and spatial variability (Grandy et al, 2006a;Harder et al, 2007;Howard et al, 1998;Hussain et al, 1999;Keim et al, 1999;Kravchenko et al, 2005;Smith et al, 2007).…”
mentioning
confidence: 99%
“…Many studies have investigated the effect of tillage system on the population density of soybean cyst nematodes, with varying results (Tyler et al, 1983(Tyler et al, , 1987Edwards et al, 1988;Koenning et al, 1995;Howard et al, 1998;Workneh et al, 1999;Chen et al, 2001;Noel and Wax, 2003). Some showed that NT prevented population increases (Tyler et al, 1983(Tyler et al, , 1987Edwards et al, 1988;Koenning et al, 1995;Workneh et al, 1999), suggesting that lower soil disturbance maintains lower soil temperatures and enhances predator nematode populations.…”
Section: Discussionmentioning
confidence: 99%